Prognostic Utility of Serum Biomarkers in Intracerebral Hemorrhage: A Systematic Review. (November 2021) - Troiani, Zachary; Ascanio, Luis; Rossitto, Christina P.; Ali, Muhammad; Mohammadi, Nicki; Majidi, Shahram; Mocco, J; Kellner, Christopher P.
Background. Intracerebral hemorrhage (ICH) accounts for 10–20% of all strokes and is associated with high morbidity and mortality. Recent studies have identified serum biomarkers as a means to improve outcome prognostication in poor grade ICH patients. Poor prognosis of ICH patients and complex pathophysiology of the disease necessitate prognostic serum biomarkers to help guide treatment recommendations. Objective. The objective is to systematically review all biomarkers used to predict long-term functional outcome in patients with spontaneous intracerebral hemorrhage. Results. We identified 36 studies investigating the predictive utility of 50 discrete biomarkers. Data from 4865 ICH patients were reviewed. Inflammatory biomarkers (11/50) were most often studied, followed by oxidative (8/50), then neuron and astrocyte-specific (7/50). S100 calcium binding protein B, white blood cell count, and copeptin were the most often studied individual biomarkers. The prognostic utility of 23 biomarkers was analyzed using receiver operating characteristic curves. Area under the curve (AUC) values for all available biomarkers except neutrophil/lymphocyte ratio were acceptable. Twenty of the 23 biomarkers were characterized by at least one excellent AUC value. Vascular endothelial growth factor, glial fibrillary astrocyte protein, and S100 calcium binding protein B were characterized by outstanding AUC. Conclusions. We identified the inflammatory and neuron and astrocyte-specific biomarker categories as having the greatest number of significant individual biomarker predictors of long-term outcome. Further investigation utilizing cross-validation of prediction models in a second independent group and blinded assessment of outcomes for the predictive utility of biomarkers in patients with ICH is warranted.